Penerapan Rebusan Air Daun Binahong Untuk Mempercepat Penyembuhan Luka Perineum Pada Ibu Post Partum - Susanti; M. Yamin; Azizah Nurcahyani (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
The World Health Organization (WHO), reports that as many 25% of MMR occur due to post partum problems.The direct factor causing the high AKI is post partum hemorrhage (45%). Post partum is the postpartum period which starts from the time the baby is born and the placenta of the baby is born so that the womb returns to what it was before pregnancy which lasts for six weeks. Post partum hemorrhage due to the opening of blood vessels in the uterus during pregnancy due to the perineal wound can cause infection, Non-pharmacological management that can be given to accelerate the healing of perineal wounds is to use binahong leaf water boiled. To find out the application of giving binahong leaf water boiled to accelerate the healing of perineal wounds in post partum mothers. This study uses a literature review study that uses literature sources in the form of books, scientific articles, especially those that have been published. By using a search through the Google Scholar database from 2015-2020. Research result Shows that there is a significant effect on the application of giving binahong leaf water boiled to accelerate the healing of perineal wounds in post partum mothers. The application of boiled water from binahong leaves is more effective in accelerating the healing of perineal wounds in post partum mothers.